Microalgal biodiesel - H. Pereira (2013)
In the latest decades, dramatic fluctuations of oil prices have occurred-owing to an increasing demand and a more and more limited supply; this situation has urged the quest for renewable energy sources. Microalgal-based biodiesel (MBB) appears as one of the most appealing and feasible substitute for fossil fuels among several cell-based sources of biodiesel. Microalgae are photosynthetic, unicellular organisms that play a vital role in CO2 sequestration in our planet-but they do not competes with food production for arable land and water supply; microalgae may indeed be grown in marginal lands, and use wastewaters or seawater as growth medium. Furthermore, they can synthesize several high added-value products, viz. bioactive compounds, polyunsaturated fatty acids and pigments, which can be extracted prior to lipid extraction itself. After processing, residual algal biomass can still be used as feedstock for other fuels, or else as animal feed. All in all, microalgae offer certainly more advantages for biofuel production than land oil crops normally used for the same purpose. Despite the numerous advantages of MBB, its economic feasibility has been hampered by excessively high (and, thus, still uncompetitive) operation costs. Attempts to effectively address this issue have encompassed either use of lipid-hyperproducing strains, or highly productive, low-cost photobioreactors-coupled with more efficient methods of harvesting and downstream processing. Additionally, full exploitation of all components in microalgal biomass-following a biorefinery strategy, should be considered to alleviate the economic constraint. This chapter addresses these possibilities in a brief, yet integrated manner.